Biotechnology 2.0 - Raúl, Isea (Journal of Current Scientific Research, 2023)
Biotechnology has changed our relationships and perspectives of the world, influencing industry and serving as a catalyst for scientific discoveries. With this change, biotechnology enters a new age known as Biotechnology 2.0. "Modern Biotechnology" and "Artificial Intelligence" are getting married. In order to lessen food poverty, this idea incorporates the most recent advancements in genetic engineering, medicine, environmental preservation, and agricultural productivity and loss reduction strategies. The importance of openness and public involvement in addressing public concerns and advancing moral behavior in biotechnology's future, fostering cooperation among diverse stakeholders, and accomplishing this in a sustainable way for the good of society and humanity cannot be overstated, especially with the backing of biotechnology governance.
Keywords: Biotechnology 2.0; Society; Industry; Biotechnology Governance; Ethical